Thrust Analysis of 250 Watt DC Motor With 12 Volt And 24 Volt - Medyawanti Pane; Billy Christian Wendo Dwisanda; Rahmad Samosir (Universitas Sultan Ageng Tirtayasa, 2022)
To reduce damage to plantation gutters due to water shock from the propeller, the team tried to make a thrust test using air as a fluid. By using a 250 Watt DC motor which gets its power from the sun's heat to drive the boat, then testing the propeller with variations in the diameter of the propeller 660 mm, 762 mm, and 812,8 mm, and testing the voltage variations at 12 volts, 18 volts and 24 volts at each propeller. Analysis of the use of solar panels required obtained as many as 2 solar panels 170 WP. From the calculation of the size of the shaft diameter that is suitable for use, it is obtained that the size of the shaft diameter is 10 mm. The results of the thrust testing obtained vary, depending on the size of the propeller diameter and voltage variations, so an adequate diameter size is obtained by using a diameter of 812,8 mm with a power of 218,2 Watt where the thrust generated is equal to 5,8 Kg. The highest current produced is 9.1 amperes, this value is qualified because it does not exceed 10 amperes. From the test results of the thrust test of the propeller, it can be concluded that the design and analysis meet the needs.